THE ANALYSIS OF ELLIPTICAL NOUN PHRASES OF THE BOOK A COMPLETE COLLECTION OF ENGLISH PROVERBS BY USING TRANSFORMATIONAL GENERATIVE GRAMMAR AT ENGLISH DEPARTMENT, ANDALAS UNIVERSITY - Haryati Haryati (English Department, Faculty of Humanities, Andalas University, 2015)
This study aims to find out the noun phrases which are missing from sentences by comparing the deep structure and surface structure in the English proverbs of John Ray’s book A Complete Collection of English Proverbs. In this research, the theory of Transformational Generative Grammar (TGG) proposed by Huddleston (1975) is applied.The data were collected with the observational method and note taking technique. In analyzing the data, the writer uses Phrase Structure Rules in revealing the constituents of the proverbs. Then, the Tree Diagram is applied in appearing the deep structure of the proverbs. After that, the writer uses Transformational Rules to observe the transformation of the deep structure into the surface structure. Furthermore, the data are presented by formal and informal ways (Sudaryanto, 1993).The writer finds two forms of noun phrase: partial and total noun phrases. The partial NPs often occur in the NP which are modified by adjectives. Meanwhile, total NPs are often occurred in the pronoun ‘you’. The selection of the NPs are based on several things, they are: because the sentence is an imperative sentence which requires the pronoun ‘you’ as the missing words, because the appearance of the pronoun in the proverbs that needs the missing words must be connected with the pronoun, and because of the verb in the proverbs which compels the missing words connected with the verb.Key words: transformational generative grammar, ellipsis, noun phrases